Public Communication Proficiency Workshop to Strengthen Students' Self-Confidence of SMKN 3 Depok - Rajagukguk, Djudjur Luciana; Salim, Agus; Lestari, Karin Septia Dwi; Isa, Danto Erfantoro (Indonesian Journal of Community Services Cel, 2023)
The ability to communicate skills is needed by everyone, especially school students. Through the spoken words and sentences, it can be seen that a person has a good personality. Developing confidence in public speaking, one of the concerns is stage fright. A person who is very fluent in everyday conversation may suddenly become terrified of having to stand up and speak in public. The purpose of the dedication is to a) increase student self-confidence; b) understand and apply public speaking techniques, c) train quick thinking, d) practice the art of verbal communication; e) and strengthening personality values by understanding effective communication that targets students at SMKN 3 Depok, Department of Automation and Office Management Expertise Competency. The method is carried out through face-to-face meetings with the technique of conducting a pre-test first, giving material, discussing then post-testing. The results obtained by students understand public speaking, there are techniques used to attract people's attention, persuade the audience to act as desired. Students can also pay attention to anything when speaking in public by gathering information on the target audience or targets to be spoken to. This ability is determined more through practice, experience and practice. The more you do it, the more skilled and confident you become.